2015
DOI: 10.1152/ajpgi.00339.2014
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-V deficiency enhances chylomicron production in lymph fistula mice

Abstract: Apolipoprotein A-V (apoA-V), a liver-synthesized apolipoprotein discovered in 2001, strongly modulates fasting plasma triglycerides (TG). Little is reported on the effect of apoA-V on postprandial plasma TG, an independent predictor for atherosclerosis. Overexpressing apoA-V in mice suppresses postprandial TG, but mechanisms focus on increased lipolysis or clearance of remnant particles. Unknown is whether apoA-V suppresses the absorption of dietary lipids by the gut. This study examines how apoA-V deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 75 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…The regulatory role of APOA5 in triglyceride metabolism has been demonstrated extensively in mice and humans, especially in liver and plasma 18 50. Recently, a novel role of APOA5 in the gut was demonstrated in APOA5 -deficient mice—APOA5 regulates lymphatic transport of dietary lipids by modulating the production of chylomicrons in the gut 51. Based on the results of this recent study and our findings, it is likely that the gut environment of carriers of the minor allele of APOA5 SNP rs651821 is different from that of non-carriers in terms of quantity and types of lipids, which may lead to unfavourable conditions of gut ecology for the growth of Bifidobacterium .…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory role of APOA5 in triglyceride metabolism has been demonstrated extensively in mice and humans, especially in liver and plasma 18 50. Recently, a novel role of APOA5 in the gut was demonstrated in APOA5 -deficient mice—APOA5 regulates lymphatic transport of dietary lipids by modulating the production of chylomicrons in the gut 51. Based on the results of this recent study and our findings, it is likely that the gut environment of carriers of the minor allele of APOA5 SNP rs651821 is different from that of non-carriers in terms of quantity and types of lipids, which may lead to unfavourable conditions of gut ecology for the growth of Bifidobacterium .…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the minor C allele in APOA5 rs651821, which increases circulating TG levels and MetS incidence, was significantly associated with reduced abundance of Bifidobacterium and its parent taxon Actinobacteria, independent of the individual's MetS status [ 31 ]. ApoA5 is known to be produced mainly in the liver but is also expressed at a low level in the intestine, and its function is to modulate chylomicron production [ 33 34 ]. Therefore, carriers of the minor C allele of APOA5 rs651821 have different lipid properties in the gut compared with non-carriers, which may lead to alteration of gut microbiota composition as mentioned above [ 31 ], suggesting a role for microbiome pattern in the regulation of ApoA5.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth considering that this property may constitute an intrinsic design feature of apoA-V, thereby allowing for retention of apoA-V by cells under certain conditions, such as following partial hepatectomy wherein apoA-V mRNA is strongly upregulated [20]. Moreover, this aspect of apoA-V trafficking may be relevant to its known occurrence as a component of bile [7,8]. The finding that apoA-V levels in bile increase in response to dietary lipid intake suggest a regulated mechanism exists to control apoA-V delivery / entry to bile.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, cell associated apoA-V has been shown to associate with cytosolic lipid droplets (LD) [6]. In addition, apoA-V has been identified as an inducible component of bile [7,8]. To date, the molecular basis for the unusual distribution of apoA-V between these tissue compartments remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%